How much do U.S. corporations know (and care) about bilateral investment treaties? Some hints from new survey evidence - Jason Webb Yackee (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
New evidence shows that top U.S. corporations are surprisingly unfamiliar with – and/or lack confidence in – bilateral investment treaties that are designed to benefit their investments in other countries. To understand whether or not such treaties "work", it is necessary to find out how and why they do, or do not, form part of firms' investment decision-making.
Keywords: 330